A4.01 T cells are critical regulators of soft callus mineralization and normal deposition of collagen I during bone repair. (24th February 2016) - Serra, A; El Khassawna, T; Petersen, A; Schlundt, C; Könnecke, I; Schell, H; Volk, HD; Radbruch, A; Schmidt-Bleek, K; Duda, G
Abstract : Background and objectives: The critical interdependency between the skeletal and immune system has been demonstrated for the fracture healing process. However, the current state of the art is contradictory. On one hand, lymphopenic mice display alleged better healing after injury. On the other hand, several studies attribute either a positive or negative role to T and B cells in bone biology, autoimmunity and fracture healing. The objective of this study is to elucidate the specific role of T and B cells in fracture repair toward early callus mineralization, bone quality, migration of osteoblast precursors and Collagen I deposition. Materials and methods: Unilateral closed femoral fractures were produced in RAG1-/-, TCR βδ chain -/-, JHT -/- and C57BL/6 wild-type mice. Bone healing was assessed by histology, biomechanical testing and fluorochrome deposition. Deposition and structural properties of CollagenI were studied by second harmonic and confocal microscopy. Callus gene expression was determined by microarray analysis. Osteoblast precursors, T and B cell migration in the callus were visualised by confocal microscopy. Results: Fractured bones of RAG -/- mice mineralized faster, but were much less capable to withstand deformation. Similarly, RAG -/- mice deposited bone quicker during the earliest phases of healing, whereas at later stages underperformed relative to controls. RAG -/- mice also failed to deposit a cross gap layer of Collagen I which correlated with diminished immigration of osteoblast precursors in the peripheral callus. The remaining network of Collagen I fibres in these mice was found to be highly disordered. Interestingly, no alteration in osteoblast precursor migration was observed when only either T or B cells were absent. However, Collagen I deposition was strongly impaired in T cell but not in B cell deficient mice. There, Collagen I fibres failed to organise across the gap in the peripheral callus displaying a highly disordered pattern of deposition. Conclusions: Overall our data show that lack of an adaptive immune system does not lead to better, but rather deregulated and suboptimal bone healing. These features were recapitulated in mice that specifically lacked T and not B cells.